Structure Design and Simulation Analysis of the Rammer Device with Crank and Gear - Liu Haitao; Gao Yuefei; Ke Biao; Su Xiaoming; Xin Yibing (Jixie chuandong)
The structure and operational principle of the rammer device with crank- link mechanism and gear and rack is introduced. Its movement is simulated by using virtual prototype technology and taking the 122 mm shell transmission as example. The theoretic calculation and simulation analysis show that,the movement of the rammer device is reliable,and under the premise of the same enforcement ramming distance and the shot velocity at the end of enforcement ramming distance,compared with the ramming by constant force,the rammer device has the advantages of short feeding time,acceleration stable and small shock to the shot at the begin time of transport.